Violence Against Women: Analysis of Murder News - Ferhan Gündüz (Anı Publishing, 2018)
In this study, the relationship between gender discrimination and violence against women is emphasized. We know that violence against women is not reacted to the same degree in every society and in different time periods. Particularly, we can observe that physical and sexual violence practices are met with reaction by societies. Nevertheless, we also find societies where the women exposed to violence are considered as responsible for violence and violence against women is culturally supported. Today, when violence and awareness of murders has increased, although similar female murders are not drawn enough attention, Özgecan Aslan's murder in Turkey caused great social reactions and remained on the agenda for days. It is important to reveal what these reactions are and how they are coming to the fore. Society obtains information about events through news in the media. Therefore, qualitative data analysis of Özgecan Aslan murder news is done by using the NVivo11 programme.